2017
DOI: 10.1080/16549716.2017.1290316
|View full text |Cite
|
Sign up to set email alerts
|

‘You’re disabled, why did you have sex in the first place?’ An intersectional analysis of experiences of disabled women with regard to their sexual and reproductive health and rights in Gujarat State, India

Abstract: ABSTRACT​Background: Globally, disabled people have significant unmet needs in relation to sexual and reproductive health (SRH). Disabled women in India face multiple discrimination: social exclusion, lack of autonomy with regard to their SRH, vulnerability to violence, and lack of access to SRH care. While they may face shared challenges, an intersectional perspective suggests that considering disabled women as a uniform and ‘vulnerable’ group is likely to mask multiple differences in their lived experiences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…Our findings are similar to studies where women with disabilities reported that healthcare providers were highly insensitive [ 43 , 52 ], rude [ 24 , 41 , 43 , 44 ], seemed to lack awareness about their needs [ 24 , 43 , 45 ], and were surprised that women with disabilities were sexually active [ 45 , 52 ]. People with disabilities also reported being denied treatment [ 22 , 44 , 53 ]. However, one study done in rural Namibia showed that people with disabilities were impressed by health care workers skills and training [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to studies where women with disabilities reported that healthcare providers were highly insensitive [ 43 , 52 ], rude [ 24 , 41 , 43 , 44 ], seemed to lack awareness about their needs [ 24 , 43 , 45 ], and were surprised that women with disabilities were sexually active [ 45 , 52 ]. People with disabilities also reported being denied treatment [ 22 , 44 , 53 ]. However, one study done in rural Namibia showed that people with disabilities were impressed by health care workers skills and training [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of sexual and reproductive health, a number of recent studies note that PWDs have been ignored in many low-income settings [14][15][16][17][18][19][20][21][22][23]. Part of the reason for this neglect is the impression that PWDs are not sexually active and less likely to marry or have children than persons without disability [14][15][16][17][18][19][20][21][22][23]. Recent evidence however shows that rates of sexual desire and activity, need for family planning services, and childbearing among disabled women are comparable to those of non-disabled women [1,19,23].…”
Section: Introductionmentioning
confidence: 99%
“…The findings presented here make visible the inherent nexus within which rights, policy, and intimate life exist (Wiseman 2019). Disabled women's fights for reproductive equality are ongoing, and systemic denial of these rights are commonplace globally (Dean et al 2017). Women's reproductive lives have become entangled in what Saunders (2020) refers to as the 'idealised reproductive citizen', where normative neoliberal processes demand the regulation of ' othered' women's reproductive decision-making as neoliberalism extends itself from market concerns to everyday life.…”
Section: Reproductive Justice and Wellbeingmentioning
confidence: 83%